Overcoming of COVID-19 Transmission: The Fulfillment of Right to Health and Education - Donna Okthalia Setiabudhi1, Irwansyah2, Toar Neman Palilingan1, Ahsan Yunus2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The spread and transmission of the virus is very fast and widespread has become a concern of all peoplein the world to prevent the transmission and overcoming of COVID-19. This paper aims to analyze thelegal aspects in overcoming COVID-19 transmission through the application of learning from home, bothfor schools and colleges. The research is a normative-legal research with statute, case and conceptualapproaches. The results show that the attention of the government is more focused on economic and healthissues and does not provide a balanced portion of education. Implementation of schooling or lectures fromhome is currently only regulated in a Ministerial Circular so that it is only a suggestion. Therefore, in orderto be able to realize the protection and fulfillment of the right to education during Covid-19 pandemic, thegovernment should issue legislation that becomes a reference for education providers and for the communityso that their right to education is still granted under any circumstances.